Using eDNA to Supplement Population Genetic Analyses for Cryptic Marine Species: Identifying Population Boundaries for Alaska Harbour Porpoises - Kim M. Parsons; Samuel A. May; Zachary Gold; Marilyn Dahlheim; Christine Gabriele; Janice M. Straley; John R. Moran; Kimberly Goetz; Alexandre N. Zerbini; Linda Park; Phillip A. Morin (Molecular Ecology, 2025)
Isolation by distance and biogeographical boundaries define patterns of population genetic structure for harbour porpoise along the Pacific coast from California to British Columbia. Until recently, inadequate sample sizes in many regions constrained efforts to characterise population genetic structure throughout the coastal waters of Alaska. Here, tissue samples from beachcast strandings and fisheries bycatch were supplemented with targeted environmental DNA (eDNA) samples in key regions of Alaska coastal and inland waters. Using a geographically explicit, hierarchical approach, we examined the genetic structure of Alaska harbour porpoises, using both mitochondrial DNA (mtDNA) sequence data and multilocus SNP genotypes. Despite a lack of evidence of genetic differentiation from nuclear SNP loci, patterns of relatedness and genetic differentiation from mtDNA suggest natal philopatry at multiple geographic scales, with limited gene flow among sites possibly mediated by male dispersal. A priori clustering of sampled areas at an intermediate scale (eastern and western Bering Sea, Gulf of Alaska and Southeast Alaska) best explained the genetic variance (12.37%) among regions. In addition, mtDNA differentiation between the Gulf of Alaska and eastern Bering Sea, and among regions within the Gulf of Alaska, indicated significant genetic structuring of harbour porpoise populations in Southeast Alaska. The targeted collection of eDNA samples from strata within Southeast Alaska was key for elevating the statistical power of our mtDNA dataset, and findings indicate limited dispersal between neighbouring strata within coastal and inland waters. These results provide evidence supporting a population boundary within the currently recognised Southeast Alaska Stock. Together, these findings will prove useful for ongoing management efforts to reduce fisheries conflict and conserve genetic diversity in this iconic coastal species.

Mobilization of porewater Pb and Zn in response to seasonal wetting and drying within contaminated floodplains - Anna M. Wade; Chris S. Eckley; Matthew Noerpel; Jennifer Goetz; David Leptich; Kim Prestbo; David Van de Riet; Steve Sluka; Richard Wilkin; Todd P. Luxton (Science of The Total Environment, 2025)

Molecular diversity of green-colored microbial mats from hot springs of northern Japan - Yangtsho Gyaltshen; Yuu Ishii; Sophie Charvet; Eleanor Goetz; Shinichiro Maruyama; Eunsoo Kim (Extremophiles, 2024)

Modeling the impacts of a changing and disturbed environment on an endangered beluga whale population - Elizabeth A. McHuron; Manuel Castellote; Gina K. Himes Boor; Kim E.W. Shelden; Amanda J. Warlick; Tamara L. McGuire; Paul R. Wade; Kimberly T. Goetz (Ecological Modelling, 2023)

New Zealand southern right whale (Eubalaena australis; Tohorā nō Aotearoa) behavioural phenology, demographic composition, and habitat use in Port Ross, Auckland Islands over three decades: 1998–2021 - Emma L. Carroll; Leena Riekkola; Virginia Andrews-Goff; C. Scott Baker; Rochelle Constantine; Ros Cole; Kim Goetz; Robert Harcourt; David Lundquist; Catherine Meyer; Mike Ogle; Richard O’Rorke; et al. (Polar Biology, 2022)
Changes in habitat availability and prey abundance are predicted to adversely influence survival and reproduction of wildlife in the Southern Ocean. Some populations of southern right whale (SRW; Eubalaena australis ) are showing dramatic changes in habitat use. Surveys were undertaken in the austral winters of 2020 and 2021 at the key nursery and socialising ground for New Zealand SRWs: Port Ross, Auckland Islands, with 548 encounters and 599 skin biopsy samples collected. Data from these two surveys spanned peak periods of use and were used to test the hypothesis there have been shifts in the phenology, demographic composition and behaviour of SRWs using the Auckland Islands over the past three decades. The behavioural phenology and demographic composition of SRW resembles that observed in the 1990s. In contrast, the proportion of groups containing cow-calf pairs increased from 20% in the 1998 survey to 50% in 2020/21. These changes are consistent with a growing population undergoing strong recruitment, not limited by food resources. Continued use of Port Ross by all SRW demographic classes confirms this as key habitat for SRW in New Zealand waters, and we support increased enforcement of existing management measures to reduce whale-vessel interactions in this remote subantarctic archipelago.

Genome editing and beyond: what does it mean for the future of plant breeding? - Tien Van Vu; Swati Das; Goetz Hensel; Jae-Yean Kim (Planta, 2022)
Main conclusion Genome editing offers revolutionized solutions for plant breeding to sustain food production to feed the world by 2050. Therefore, genome-edited products are increasingly recognized via more relaxed legislation and community adoption. Abstract The world population and food production are disproportionally growing in a manner that would have never matched each other under the current agricultural practices. The emerging crisis is more evident with the subtle changes in climate and the running-off of natural genetic resources that could be easily used in breeding in conventional ways. Under these circumstances, affordable CRISPR-Cas-based gene-editing technologies have brought hope and charged the old plant breeding machine with the most energetic and powerful fuel to address the challenges involved in feeding the world. What makes CRISPR-Cas the most powerful gene-editing technology? What are the differences between it and the other genetic engineering/breeding techniques? Would its products be labeled as "conventional" or "GMO"? There are so many questions to be answered, or that cannot be answered within the limitations of our current understanding. Therefore, we would like to discuss and answer some of the mentioned questions regarding recent progress in technology development. We hope this review will offer another view on the role of CRISPR-Cas technology in future of plant breeding for food production and beyond.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Blue Carbon Storage in a Northern Temperate Estuary Subject to Habitat Loss and Chronic Habitat Disturbance: Cowichan Estuary, British Columbia, Canada - Tristan J. Douglas; Goetz Schuerholz; S. Kim Juniper (Frontiers in Marine Science, 2022)
Vegetated coastal ecosystems can contribute greatly to long-term carbon sequestration and greenhouse gas emission mitigation, providing a strong argument for their protection and restoration. We investigated carbon sequestration in the Cowichan Estuary, a temperate estuary on Vancouver Island, Canada, in relation to habitat type (salt marsh, eelgrass, mudflats, and oyster shell beds) and habitat degradation. Stored organic carbon and inorganic carbon were quantified in the top 20 cm of sediment as well as in eelgrass and salt marsh vegetation. Sedimentation and carbon sequestration rates were quantified by 210 Pb radiometric dating, and organic matter sources and quality were assessed by δ 13 C, C:N ratios and photopigment content. We also examined the potential impact of habitat disturbance by industrial activity (log booms) on the estuary’s carbon storage capacity. The salt marsh was the most important carbon reservoir, with a mean sediment organic carbon stock of 58.78 ± 19.30 Mg C ha -1 . Sediment organic carbon stocks in the upper mudflats, lower mudflats, eelgrass meadow, and oyster shell beds were 19.30 ± 3.58, 17.33 ± 3.17, 18.26 ± 0.86 and 9.43 ± 1.50 Mg C ha -1 , respectively. Carbon accumulation rates in the salt marsh and eelgrass meadows were 68.21 ± 21 and 38 ± 26 g C m -2 yr -1 , whereas 210 Pb profiles indicated that mudflat sediments were subject to erosion and/or mixing. While eelgrass was absent from the log boom area, likely due to disturbance, sediments there had similar carbon sequestration and bulk properties to adjacent mudflats. Carbon stocks in the eelgrass meadow were similar to those of the mudflats and consistent with the relatively low values reported for other temperate Zostera marina meadows, compared with tropical eelgrass meadows. Stable isotope evidence was suggestive of substantial outwelling and/or decomposition of eelgrass vegetation. Finally, we compared the carbon sequestration potential of the estuary to selected sources and sinks of CO 2 in the surrounding region. We estimated that annual carbon sequestration in the estuary offsets approximately twice the greenhouse gas emission increases attributable to local population growth, and is equivalent to approximately twice that of a 20-year-old stand forest.

Animal-Borne Telemetry: An Integral Component of the Ocean Observing Toolkit - Rob Harcourt; Ana M. M. Sequeira; Xuelei Zhang; Fabien Roquet; Kosei Komatsu; Michelle Heupel; Clive McMahon; Fred Whoriskey; Mark Meekan; Gemma Carroll; Stephanie Brodie; Colin Simpfendorfer; et al. (Frontiers in Marine Science, 2019)

Matrix detachment and proteasomal inhibitors diminish Sulf-2 expression in breast cancer cell lines and mouse xenografts - Ashwani Khurana; Deok Jung-Beom; Xiaoping He; Sung-Hoon Kim; Robert C. Busby; Laura Lorenzon; Massimo Villa; Alfonso Baldi; Julian Molina; Matthew P. Goetz; Viji Shridhar (Clinical & Experimental Metastasis, 2013)